Characterization and transcriptomic basis of biofilm formation by Lactobacillus plantarum J26 isolated from traditional fermented dairy products. (May 2020) - Sun, Linlin; Zhang, Yu; Guo, Xiaojie; Zhang, Lidong; Zhang, Wei; Man, Chaoxin; Jiang, Yujun
Abstract: A total of 79 lactic acid bacteria (LAB) isolated from traditional fermented dairy products in China were evaluated for the biofilm forming capacity using microtiter plates. Out of all LAB tested, 74 strains were able to form biofilm on abiotic surfaces and highly strain-specific. In particular, Lactobacillus plantarum J26 showed most potent activity for biofilm formation and could grow as biofilm observed by scanning electron microscopy (SEM). Thus, the objective of this work was to investigate the characterization of biofilm formed by L. plantarum J26 and elucidate the underlying metabolic pathways based on transcriptomic sequencing. The results showed that 1051 genes were significantly differentially expressed in planktonic and biofilm conditions, of which 513 genes were up-regulated and 538 genes were down-regulated. Meanwhile, these genes were involved in such pathways as pyrimidine and glycerine metabolism, amino acids biosynthesis and stress response. In addition, extracellular enzymes ( lp3014 and lp284 ), aspartate aminotransferase ( pyrB ), propylene glycol dehydrogenase ( dhaT ) and quorum sensing ( luxS ) played important roles in biofilm formation by L. plantarum J26. To sum up, these findings suggested that L. plantarum J26 could be useful for improving performance in the food industry and maintain probiotic functions in the gastrointestinal tract by forming biofilm. Highlights: Biofilm forming capacity of LAB was evaluated. SEM was used to distinguish planktonic and biofilm growth. Biofilm formation related to adhesion and tolerance ability. lp3014, lp284, pyrB, dhaT and luxS genes played a role in biofilm formation.